2021
DOI: 10.1016/j.jeurceramsoc.2020.07.056
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation/corrosion of BN-based coatings as prospective interphases for SiC/SiC composites

Abstract: The ceramic matrix composites envisaged as structural parts in the hot section of aircraft engines consist of SiC-based fibres and matrices with a BN interphase coating between them. To control their service life, the oxidation/corrosion behaviour of these materials must be determined. For this purpose, samples of different geometries were prepared by chemical vapour deposition and thermally subjected to wet air. The behaviour of BN alone depends on its crystallization degree, structural homogeneity and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…No references were found on modeling for CMCs, though experimental studies o ing process have been reported. Studies o derived SiC ceramic 25 and SiC/SiC c shown that porosity decreases and mecha prove with the increasing number of PIP show that increasing pyrolysis temperatu tration of SiC fillers in polycarbosilane improved mechanical properties in two-d SiC (C/SiC) composites fabricated using Starting with pyrolysis of a "cured prepreg-based composite, each processin process involves infiltration of a precera porous ceramic preform followed by a py which the polymer is converted into ceram cess modeling is focused on these two ste Modeling of infiltration of liquids in well-studied subject, especially in the where it is used to model seepage of wa soils and rocks. 29,30 The physics of resin under pressure is similar to the seepage pr lar approaches have been used also to mod into a mold containing fiber mats.…”
Section: Sic Fibersmentioning
confidence: 99%
See 3 more Smart Citations
“…No references were found on modeling for CMCs, though experimental studies o ing process have been reported. Studies o derived SiC ceramic 25 and SiC/SiC c shown that porosity decreases and mecha prove with the increasing number of PIP show that increasing pyrolysis temperatu tration of SiC fillers in polycarbosilane improved mechanical properties in two-d SiC (C/SiC) composites fabricated using Starting with pyrolysis of a "cured prepreg-based composite, each processin process involves infiltration of a precera porous ceramic preform followed by a py which the polymer is converted into ceram cess modeling is focused on these two ste Modeling of infiltration of liquids in well-studied subject, especially in the where it is used to model seepage of wa soils and rocks. 29,30 The physics of resin under pressure is similar to the seepage pr lar approaches have been used also to mod into a mold containing fiber mats.…”
Section: Sic Fibersmentioning
confidence: 99%
“…21 BN coatings are another choice for SiC f because the liquid B 2 O 3 resulting from BN oxidation can heal pores and cracks at high temperatures, making it wider potential applications than those of PyC at oxygen-sensitive environments. [23][24][25] The toughening effects of BN coatings depend on their crystallization degree and structural homogeneity when coated with SiC f . 25 The single-/double-layer BN-coated SiC f by chemical vapor infiltration method has confirmed to effectively increase the strength of the SiC/ SiC composites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coating will reduce the area of carbon fiber exposed to oxygen atmosphere, thus improving the oxidation resistance of the composites Therefore, Chemical vapor deposition (CVD), chemical vapor infiltration (CVI), and hydrothermal methods can be used to prepare coatings on carbon fiber surface [1,17,20]. The types of coatings can include C coating [21], BN coating [22], SiC coating [23], etc. These coatings can not only change the surface roughness of carbon fiber but also improve the interface bonding performance between ceramic matrix and carbon fiber reinforcement.…”
Section: Introductionmentioning
confidence: 99%